2012
DOI: 10.1007/s00441-011-1298-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic tubular nanofiber mesh and platelet rich plasma-mediated delivery of BMP-7 for large bone defect regeneration

Abstract: There is a growing need for successful bone tissue engineering strategies and advanced biomaterials that mimic the structure and function of native tissues carry great promise. Successful bone repair approaches may include an osteoconductive scaffold, osteoinductive growth factors, cells with an osteogenic potential and capacity for graft vascularisation. To increase osteoinductivity of biomaterials, the local combination and delivery of growth factors has been developed. In the present study we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 30 publications
1
45
0
3
Order By: Relevance
“…We subsequently took the next step towards clinical translation by performing small animal studies using rat, mice and rabbit models (207)(208)(209). As reviewed in detail in Reference (200), we were able to demonstrate the in vivo capability of our composite scaffolds in combination with growth factors or cells to promote bone regeneration within ectopic sites or critical sized cranial defects in the small animal models.…”
Section: Taking Composite Scaffold Based Bone Tissue Engineering Frommentioning
confidence: 95%
“…We subsequently took the next step towards clinical translation by performing small animal studies using rat, mice and rabbit models (207)(208)(209). As reviewed in detail in Reference (200), we were able to demonstrate the in vivo capability of our composite scaffolds in combination with growth factors or cells to promote bone regeneration within ectopic sites or critical sized cranial defects in the small animal models.…”
Section: Taking Composite Scaffold Based Bone Tissue Engineering Frommentioning
confidence: 95%
“…In line with this, superior bone formation was shown in bicortical mandible defects in rabbits treated with a composite of porous bone mineral and bio-guide membrane supplemented with PRP containing 699 × 10 3 platelets/µL (4.4-fold enrichment) [46]. It was also suggested that PRP can be utilized for the delivery of BMP-7 within a calcium phosphate-coated nanofiber mesh tube, where BMP-7 delivery enhanced bone formation and biomechanical properties in rat segmental femur defects [47].…”
Section: Prp In Tissue-engineered Constructsmentioning
confidence: 99%
“…The scaffolds were produced by fused deposition modeling, as previously reported [17,25]. To enhance the osteoinductive properties of the scaffold, the surface was coated with a layer of calcium phosphate (CaP) using a previously published protocol [28]. The scaffolds had a porosity of 74% and a 0/90°lay down pattern.…”
Section: Scaffold Design and Preparationmentioning
confidence: 99%